MENGGUGAT MODEL EVALUASI KOGNITIF DALAM PAI SEBAGAI PENGHAMBAT PENDEWASAAN IMAN - Nasrullah Nasrullah (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
Assessment in Islamic Religious Education (PAI) has long been dominated by a cognitive-oriented approach, focusing on material mastery, memorization, and formal accuracy. Such evaluation models have drawn criticism for their failure to reflect the depth of students’ faith and piety. This study aims to evaluate the impact of cognitive-dominated assessments on students' faith development and to propose a more holistic approach. Using a descriptive qualitative method, the research was conducted in several junior high schools in Banda Aceh. Data were collected through in-depth interviews, classroom observations, and document analysis of assessment instruments. The findings reveal that cognitively focused evaluations tend to neglect students’ affective and spiritual dimensions. This results in shallow, ritualistic faith with minimal moral reflection. The study underscores the need for a transformative evaluation model in PAI that integrates spiritual reflection, religious experiences, and moral awareness. The implications highlight the urgency of designing religious assessments that genuinely shape students’ religious character in the current context of moral complexity.